Fate of Listeria monocytogenes and Salmonella Typhimurium in homemade marinade and on marinated chicken drumsticks, wings and breast meat - Incili, Gokhan Kursad; Akgol, Muzeyyen; Aydemir, Mehmet Emin; Alan, Selcuk; Mutlu, Muhsin; Ilhak, Osman Irfan; Oksuztepe, Gulsum (Elsevier, 2020)
In recent years, the increase in consumer demands for the products that are processed with natural additives has highlighted the use of natural substances in food processing and safety. For this purpose, the aim of this study is to determine the effect of homemade marinade that are prepared with the natural substances existing in every kitchens and restaurants on Salmonella Typhimurium, Listeria monocytogenes and natural microbiota of chicken wings, drumstick and breast meats. The results of this study revealed that the number of Salmonella Typhimurium decreased about 4.0 log(10) in 24 h in marinade sauce, while no significant change was observed in the number of Listeria monocytogenes. The number of Salmonella Typhimurium decreased 0.9 and 1.4 log(10) in the marinated chicken wing and breast meat. Marinade has a strong bacteriostatic effect on Listeria monocytogenes, total mesophilic aerobic bacteria and psycrotmphic bacteria in the wing, drumstick and breast meats. The numbers of L. monocytogenes, TMAB and psychrotrophic bacteria in marinated groups were 1.0-3.0 log(10) lower than control groups at the end of the storage. The marinades that people can prepare with the natural ingredients existing in their kitchen would enable microbiologically more reliable chicken meats.
Keywords: Chiken meat products; Marination; Salmonella typhimurium; Listeria monocytogenes